Design, synthesis, and conformational analysis of 3-cyclo-butylcarbamoyl hydantoins as novel hydrogen bond driven universal peptidomimetics. Issue 4 (6th December 2017) - Bellucci, M. C.; Frigerio, M.; Castellano, C.; Meneghetti, F.; Sacchetti, A.; Volonterio, A.
Abstract : 3- cyclo -Butylcarbamoyl hydantoins are able to mimic α-helix and β-turn secondary structures as assessed by molecular modeling, NMR studies, and X-ray analysis. Abstract : A collection of systematically substituted 3- cyclo -butylcarbamoyl hydantoins was synthesized by a regioselective multicomponent domino process followed by easy coupling reactions. Calculations, NMR studies and X-ray analysis show that these scaffolds are able to project their side chains similar to common secondary structures, such as the α-helix and β-turn, with favourable enthalpic and entropic profiles.